2022
DOI: 10.1177/15347354221092706
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Conventional and Photodynamic Therapy for Treatment of Cervical Cancer with Cannabidiol

Abstract: Cervical cancer (CC) is the fourth most diagnosed cancer in women worldwide. Conventional treatments include surgery, chemo- and radiotherapy, however these are invasive and may cause severe side effects. Furthermore, approximately 70% of late-stage CC patients experience metastasis, due to treatment resistance and limitations. Thus, there is a dire need to investigate alternative therapeutic combination therapies. Photodynamic therapy (PDT) is an alternative CC treatment modality that has been clinically prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…(2019) revealed that the surface functionalization of these lipid nanocapsules with CBD allowed cannabinoid receptors overexpressed in glioma cells to be targeted, as shown in permeability experiments across the BBB of an in vitro model and in biodistribution experiments in mice [ 104 ]. When testing cannabinoid nanoparticles on other cancer models, the results showed enhancement of photodynamic therapy in combination with cannabinoids in colorectal [ 105 ], cervical [ 106 ] and breast cancer [ 107 , 108 , 109 ]. CBD in combination with nanomiceles was studied in triple-negative breast cancer [ 110 ], and with lipid nanoparticles in ovarian cancer [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…(2019) revealed that the surface functionalization of these lipid nanocapsules with CBD allowed cannabinoid receptors overexpressed in glioma cells to be targeted, as shown in permeability experiments across the BBB of an in vitro model and in biodistribution experiments in mice [ 104 ]. When testing cannabinoid nanoparticles on other cancer models, the results showed enhancement of photodynamic therapy in combination with cannabinoids in colorectal [ 105 ], cervical [ 106 ] and breast cancer [ 107 , 108 , 109 ]. CBD in combination with nanomiceles was studied in triple-negative breast cancer [ 110 ], and with lipid nanoparticles in ovarian cancer [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…Articles selection : The prerequisites for inclusion were as follows: Articles have outlined the contributions the MCPyV makes to SCCs and ACs. However, the following exclusion standards were taken into account: ( 1 ) Reviews; ( 2 ) non-English language; ( 3 ) Case reports; ( 4 ) Articles not concentrating on the contributions of the MCPyV to SCCs and ACs; ( 5 ) Articles deficient in important information; and ( 4 ) Studies without full text.…”
Section: Methodsmentioning
confidence: 99%
“…Cervical cancer is cancer arising from the cervix ( 1 ). It is due to the abnormal growth of cells that can invade or spread to other body parts ( 2 , 3 ). Worldwide, cervical cancer is the fourth most common cause of cancer and death from cancer in women ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Red light activation of the PS results in the production of singlet oxygen ( 1 O 2 ) and harmful ROS. This cytotoxic species production causes oxidative stress, which may lead to apoptosis (Razlog et al, 2023). Although, it has been established that PDT is a tumor‐specific therapeutic criteria, its uses are severely hampered by the hypoxic tumor microenvironment (TME) (Hu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%